Evaluation of Biomass Development Policies and Strategies for Sustainable Energy - Nurus Shofiyana; Rejang Musi Agastya S.W; Muhammad Uwais Al-Qarni; Imam Supriyadi (East Asian Journal of Multidisciplinary Research, 2022)
Fossil energy is a threat to Indonesia. The national primary energy mix is dominated by coal, while many foreign investors are aiming for Indonesia's biomass to be used as a power plant. It would be ironic if foreigners controlled it. Policies and regulations in the energy sector are needed for managing and utilizing existing resources. Using descriptive qualitative research methods aims to understand the phenomena experienced by the research subjects. Implementing policies and strategies for developing biomass for sustainable energy is also related to purchasing renewable energy, developing small-scale Biomass Powerplant management in the frontier, outermost and underdeveloped areas, utilization of wastes, municipal waste, and Co-firing systems in existing Coal Powerplant. Policy adjustments are urgently needed regarding using biomass to accelerate the renewable energy mix along the issues to maintain sustainability.